Integration of Arabic Language Education and Islamic Religious Education in the Era of Globalization and Disruption: A Systematic Review of Literature on Curriculum Models, Innovations, and Transformations (2013–2025) - Siti - Zuhriyeh; Daniel Arief Budiman; Asep Mulyana; Tamsik Udin (EL-IBTIKAR: Jurnal Pendidikan Bahasa Arab, 2025)
The era of globalization and disruption necessitates the integration of Arabic Language Education (PBA) and Islamic Religious Education (PAI) within a value-based curriculum aligned with 21st-century competencies. This article systematically reviews scientific literature on curriculum integration models, innovations, and transformations of PBA–PAI from 2013 to 2025. Using a Systematic Literature Review (SLR) approach, 82 articles were analyzed from databases such as Scopus, WoS, DOAJ, and Garuda. The findings reveal three major integration models: thematic-integrative, interdisciplinary, and structural-integrative. Educational innovations include LMS, AI-based chatbots, flipped classrooms, and gamification of Islamic values. The curriculum transformation moves toward a transdisciplinary approach, emphasizing contextual learning and character building. This study concludes that integrating PBA–PAI is both an educational and philosophical strategy relevant to strengthening students' religious and linguistic competencies. The results serve as a foundation for policy formulation and further research on integration effectiveness.